BALINESE ORNAMENTS IN BALE GILI BUILDING ARCHITECTURE ACCULTURATION - Ni Made Witrishna Artistiari (Riset Arsitektur (RISA), 2017)
Abstract - The cultural from of acculturation that has been taking place in Indonesia since the arrival of foreign traders who colonized Indonesia and influenced its traditional architectural culture with non-local architecture yielded a new hybrid form called the Dutch East Indies style. This forms real, tangible evidence of the presence of non-local cultural acculturation with Indonesian indigenous culture. The Bale Gili building at the Soekasada Ujung Park is one example of this phenomenon, built in the Dutch Colonial Era by a Dutch architect named Van Den Hentz. The impact made by Dutch colonial architecture is immediately apparent, but there are also Balinese ornaments in the entire scope of the Water Palace that must be taken into account. The dominant ornaments, their role and significance in the architectural acculturation process and the extent of this acculturation between local and non-local (Dutch) architecture in the Bale Gili building need to be explored by way of extending the acculturation of this typical Indies type of architecture.The descriptive method has been employed to interpret the concrete presence of the Bale Gili building, followed by the analytical method applied to the object of research, subsequently correlated with theoretical study of the ornamentation in the architecture of the building in addition to its anatomical theory. The findings show that the dominant ornaments in the Bale Gili building are the ones based on religion and local beliefs. A closer examination of the ornaments by way of extending architectural acculturation indicates that these ornaments based on religious beliefs in this particular building reveal a concrete form of acculturation between the Dutch colonial style of architecture and the Balinese traditional style. Keywords: Acculturation, Architecture, Dutch East Indies architecture, Water Palace, Bali, Ornament, Bale Gili